QUO VADIS KHILAFATISME: SEBUAH KENISCAYAAN ATAU ANCAMAN DALAM DISKURSUS IDEOLOGI REPUBLIKAN PANCASILAIS - Rendy Adiwilaga (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2020)
Having an advantage of being the majority in Indonesia makes the Islamic ideologies particularly the ideology of Islamic Khilafah spreads easily amongs the Indonesian moeslim. Furthermore, those who believe in the ideology of Islamic Khilafah also believe that this ideology is the solution to the problem of the nation such as poverty, unemployement, amorality etc. Historically, the concept of Islamic Khilafah tells that a secular nation is unacceptable and the nation of the Islamic Khilafah is the absolute answer to that. This article elaborates the value of the Islamic notions proposed by Islamic sholars, formal instutions or even Hizbu Tahrir then compares them to the value of Pancasila. In this article, I compare many references regarding Islamism, Khilafatism, and Pancasilaism, and then present them in a critical narration. In short, the optimism to the value of Pancasila rises due to the fact that Islam is apparently one of the foundations of Pancasila. In the other hand, I reckon that the ideology of Islamic Khilafah is a failed product due to its nature of violence and absoluteness which make the ideology and the followers stuck in their comfort zone and their claim of righteousness.